Distribution of Acute Phase Proteins in Post-SARS CoV2 Mucormycosis Infection - Dixit, Deepti; Shettar, Vishwanath G; Joshi, Vikas; Javalgi, Anita P; Athanikar, Vidisha S; H, Kavana (Annals of Pathology and Laboratory Medicine, 2024)
Background This study was aimed to estimate the serum levels of acute phase reactants/proteins (APR) which includes serum ferritin, C Reactive Protein, D-dimer and Procalcitonin in mucormycosis infection following SARS CoV2 infection and to determine the clinical, biochemical and histopathological findings in the same. Methods It was an observational cross-sectional study. All cases of mucormycosis following SARS CoV2 infection were reviewed. Demographic and clinical details with comorbidities and relevant laboratory investigations which included serum glucose, serum ferritin, C Reactive Protein, D-dimer, Procalcitonin were noted at the time of diagnosis of mucormycosis. Diagnosis of mucormycosis was based on frozen section examination and histopathological examination. Results Thirty-two cases of mucormycosis following SARS CoV2 infection confirmed on histopathology were studied. Majority of the cases (77%) were with comorbidity especially having diabetic mellitus type 2. C-Reactive protein, Procalcitonin and serum Ferritin were raised in almost all cases with mean of 80.92±62.5mg/l, 17.99±26.87ng/ml. and 464.9±422.03ng/ml respectively. D Dimer was raised in less than 50% cases with a mean of 828.5±245.9 ng/ml. Conclusion Acute phase proteins like C reactive Protein, Procalcitonin, Serum ferritin and D Dimer were raised in Post-SARS CoV2 infected individual who presented now with mucormycosis infection. These markers were raised markedly in critically ill patients thus indicated its pathogenetic role in severe morbidity, thus estimation of serum acute phase reactants can help in predicting the course and severity of illness.